Importance of standardization in Wide Area Network capacity management for future cost optimization - Sinha, Sudip; Das, Anirban; Ghosh, Amitava (International Journal of Engineering and Technology, 2018)
For Enterprise organization, IT (Information Technology) budget is getting reduced and Organizations are focusing on optimizing Operating cost to save money which can be used in Security enhancement to protect the IT / OT (Production) asset or in innovative solution deployment to get competitive advantages in the market [1] [2]. As in the technologies are undergoing paradigm shift from closed end to open ended (cloud / IoT centric) Solution and customer needs secured connectivity for reliable service delivery, Next Gen solution approach must be standardized for easy governance for the future.Â Â